From Jericho to Argeș, Deva, Dynas Emrys, and Surami: The Myth of Construction Between Curse and Sacrifice (De la Jericho la Argeș, Deva, Dynas Emrys și Surami: Mitul creației între blestem și sacrificiu) - Tomasz Klimkowski; Emilia Ivancu (Incursiuni în imaginar)
The present article aims at a comparative analysis amongst four legends constructed around the same myth i.e. the myth of construction that requires a sacrifice: the Romanian ballad about the construction of the monastery in Argeș, Wallachia, the Hungarian ballad about the construction of the fortress of Deva in Transylvania, Romania, the Welsh legend of Dynas Emrys and the Georgian legend about the construction of the Surami fortress. Each of the four versions brings forth a certain particularity: the paradox of walling in a woman and her child for a church in the Romanian ballad, the burning of the woman, and then her ashes walled in in the Hungarian version, the avoiding of the sacrifice in the Welsh legend, and the transformation of the sacrifice into self-sacrifice in the Georgian one. Moreover, through a comparative analysis of different versions of the Bible, we shall emphasise the importance of the building of the city of Jericho, the relevance of curse and sacrifice around it as both a source and a propagation of the myth. For our research, we shall use the methodology devised by Mircea Eliade in his book about the myth of sacrifice (Meșterul Manole. Studii de etnologie și mitologie, 2007), as well as the works of Professor Trumbull, The Threshold Covenant (1896) and The Blood Covenant (1898). One of the main conclusions of our article is that nothing built by man has a soul, and that can only last if it only acquires a soul. Hence the sacrifice that has been part of man’s history since times immemorial. Any revisitation of this myth can only bring people together and thus emphasise the things people and peoples have in common, and that can only lead of a better understanding of the Other.